STUDI TENTANG ALAT MUSIK TRADISIONAL SUMATERA SELATAN PADA PENDIDIKAN ANAK USIA DINI (PAUD) - Aisyah Ulfa; Syafdaningsih syafar; Rukiyah Rukiyah (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
This study entitled The Study of Traditional Musical Instruments of South Sumatra in Early Childhood Education (PAUD) and held on 4 to 11 September 2017 conducted at the State Museum of South Sumatra and the Department of Culture. The method used is descriptive qualitative, which has the purpose to describe the traditional musical instruments that exist in South Sumatra in Early Childhood Education (PAUD). Data collection techniques using observation sheets, interviews, and documentation. From the results of research can be concluded that the traditional musical instruments during the Sultanate of Palembang, traditional musical instruments influenced many Islamic and Arabic culture. Judging from the material of making and how to play it by beating, traditional musical instrument has a very important function in early childhood that is able to develop aspects of physical and motor development of emotional social in early childhood. Of the 14 traditional musical instruments contained in South Sumatra, there are 11 traditional musical instruments that are still developing to date and identified 2 identifiers of traditional musical instruments that can be played by young children. The two instruments are traditional Tunggung / Rebana musical instruments from South Sumatra and traditional Burda musical instruments from Ogan Komering Ulu (OKU) area. Both traditional musical instruments that can be played by early childhood, because see from the material making and how to play it by being hit using the fingers of the hand that can train the fine motor aspects of the child.